2009
DOI: 10.1007/s00572-009-0276-8
|View full text |Cite
|
Sign up to set email alerts
|

Response of mycorrhizal periwinkle plants to aster yellows phytoplasma infection

Abstract: The objective of our research was to assess if arbuscular mycorrhizal (AM) fungal colonization can modify the effect of infection by two aster yellows phytoplasma strains (AY1, AYSim) in Catharanthus roseus plants. Both phytoplasma strains had a negative effect on the root fresh weight, but they differed in symptoms appearance and in their influence on photosynthetic and transpiration rates of the periwinkle plants. AM plants showed significantly reduced shoot fresh weight, while the transpiration rate was sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…L. asiaticusinfected citrus were reduced after the application of Pi. In the case of phytoplasmas, although the correlation between Pi and the disease symptoms remains unclear, the disease symptoms in phytoplasma-infected plants could be reduced by the application of AM fungi (Lingua et al, 2002;Romanazzi et al, 2009;Kami nska et al, 2010;Sampò et al, 2012). AM fungi are symbiotic organisms that are able to enhance the uptake of Pi through up-regulation of Pi starvation responses in host plants (Branscheid et al, 2010;Gu et al, 2010;Volpe et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…L. asiaticusinfected citrus were reduced after the application of Pi. In the case of phytoplasmas, although the correlation between Pi and the disease symptoms remains unclear, the disease symptoms in phytoplasma-infected plants could be reduced by the application of AM fungi (Lingua et al, 2002;Romanazzi et al, 2009;Kami nska et al, 2010;Sampò et al, 2012). AM fungi are symbiotic organisms that are able to enhance the uptake of Pi through up-regulation of Pi starvation responses in host plants (Branscheid et al, 2010;Gu et al, 2010;Volpe et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Colonization by AM fungi can modify the plants' root architecture and enhance the uptake of mineral nutrients, in particular Pi (Gu et al, 2011;Volpe et al, 2013). Interestingly, several studies also reported that AM fungi reduce the disease symptoms caused by phytoplasmas (Lingua et al, 2002;Romanazzi et al, 2009;Kami nska et al, 2010;Sampò et al, 2012).…”
mentioning
confidence: 99%
“…Alternative approaches are thus required to reduce the spread of such diseases. Some interesting studies about the interactions between potential biocontrol agents or resistance-inducer micro-organisms, phytoplasmas and host plants or insect vectors have been published recently (Lingua et al 2002;Lherminier et al 2003;Marzorati et al 2006;Kamiń ska et al 2010). The endophyte population within crop plants has been shown to influence their susceptibility to disease, but the role of endophytic micro-organisms in relation to phytoplasma diseases and to spontaneous 'recovery' has still to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to phytoplasmas, specialized obligate parasites of phloem tissue that are transmitted by insect vectors, most reports show a reduction of disease incidence (Kamińska et al, 2010a(Kamińska et al, , 2010bBatlle et al, 2011;D'Amelio et al, 2011). However, it should be noted that the analysis of mycorrhizal effects on phytoplasmas and viruses is difficult because of the potential impact of mycorrhization on the insect vector and the complexity of studies on multi-trophic interactions.…”
Section: Mycorrhiza Effects On Above-ground Interactionsmentioning
confidence: 95%